Meningkatkan Aktivitas dan Keterampilan Berpikir Kritis Melalui Model PBL, CRH, dengan Pendekatan TPACK pada Siswa Kelas 5 - Riska Amalia; Radiansyah (CV. ITTC INDONESIA, 2023)
The problem in this study is low activity, critical thinking skills and student acquisition results in the material of rights and obligations. This study aims to describe teacher activities, analyze activities, critical thinking skills and further develop student learning outcomes. This research used PTK which was completed in 3 meetings. The research location was at SDN Teluk Dalam 12 Banjarmasin Class 5 which amounted to 20 students. The types of data in this study are qualitative and quantitative data, obtained through observation and individual written test measurement techniques. The indicator of research success is ≥82% or a score of ≥70. The results of the review showed that the educator's movement at each gathering faced an increase, initially getting a score of 25 increased to a score of 31 (very good). Student activity at meeting 1 got 50% increased at meeting 3 to 100% (very active). Critical thinking skills initially 50% increased to 100% (very high). The classical completeness of student learning outcomes increased significantly, originally 50% complete and increased to 100%, it can be concluded that the implementation of the Problem Based Learning model, Course Review Horay, and TPACK Approach with teacher activities carried out very well can increase activity, critical thinking skills and student learning outcomes.